Identification of the coefficient in the diffusion model of hydrodynamic flow in a chemical reactor - Gamzaev, Kh. M.; Bayramova, N. Kh. (Національний технічний університет "Харківський політехнічний інститут", 2024)
A chemical technological process taking place in a chemical reactor with a second-order chemical reaction is considered. A one-parameter diffusion model for nonstationary flows is proposed for the mathematical description of the hydrodynamic flow in the reactor. Within the framework of the proposed model, the task is set to identify the longitudinal mixing coefficient according to an additionally specified condition regarding the concentration of the reagent under study at the outlet of the reactor. A special representation is proposed for the diffusion terms in the hydrodynamic flow model in the reactor. The method of difference approximation is used to construct a discrete analogue of this model using explicit-implicit time approximation for diffusion terms. Decomposition is used to numerically solve the resulting system of linear difference equations, as a result of which the system of difference equations for each discrete value of a time variable splits into two mutually independent linear subsystems, each of which can be solved independently, independently of each other. As a result, an explicit formula was obtained for determining the approximate value of the longitudinal mixing coefficient in a hydrodynamic flow. Based on the proposed computational algorithm, numerical calculations were performed for model problems.

Розглядається хіміко-технологічний процес, що протікає у хімічному реакторі, з хімічною реакцією другого порядку. Для математичного опису гідродинамічного потоку в реакторі пропонується однопараметрична дифузійна модель нестаціонарних потоків. В рамках запропонованої моделі поставлено завдання ідентифікації коефіцієнта поздовжнього перемішування додатково заданою умовою щодо концентрації досліджуваного реагенту на виході з реактора. Пропонується спеціальне подання для дифузійних членів моделі гідродинамічного потоку в реакторі. Методом різницевої апроксимації будується дискретний аналог даної моделі з використанням явно-неявної апроксимації за часом для дифузійних членів. Для чисельного рішення отриманої системи лінійних різницевих рівнянь застосовується декомпозиція, у результаті система різницевих рівнянь при кожному дискретному значенні тимчасової змінної розпадається дві взаємно незалежні лінійні підсистеми, кожна з яких може вирішуватися самостійно, незалежно друг від друга. В результаті отримана явна формула для визначення наближеного значення коефіцієнта поздовжнього перемішування гідродинамічному потоці. На основі запропонованого обчислювального алгоритму було проведено чисельні розрахунки для модельних завдань.
Ідентифікація коефіцієнта дифузійної моделі гідродинамічного потоку в хімічному реакторі
Keywords: diffusion model; longitudinal mixing coefficient; coefficient inverse problem; explicit-implicit approximation; хіміко-технологічні процеси; нестаціонарні потоки; явно-неявна апроксимація; коефіцієнт поздовжнього перемішування